THE ROLE OF INDIVIDUAL CHARACTERISTICS AND SOCIAL CAPITAL ON COMMUNITY INCOME IN SERANGAN TOURISM VILLAGE - Putu Sindy Riananda Puteri; Ni Made Tisnawati (Adisam Publisher, 2025)
This study is motivated by the importance of understanding the factors that influence community income in Serangan Tourism Village. The objective of this research is to analyze the role of social capital in moderating the effect of individual characteristics on community income. This study is expected to provide deeper insight into the dynamics occurring within this sector and to support the development of more effective policies.The research employs a quantitative approach using the Moderated Regression Analysis (MRA) method. Data analysis was conducted to examine the effect of the independent variable (individual characteristics) on the dependent variable (community income), and the moderating role of social capital in altering the strength or direction of the relationship between individual characteristics and community income.The results reveal that individual characteristics (X) have a significant effect on the income of the community in Serangan Tourism Village (Y). The MRA test indicates that social capital, acting as a moderating variable, weakens the effect of individual characteristics on income. This finding highlights the importance of developing strong social networks, trust, and collaboration to improve access to information that can enhance income generation. Nevertheless, individual characteristics remain essential as a fundamental basis for individuals to earn income.